Optical Fiber Bending Detection on Long Distance OPGW using OTDR - M. F. M. Salleh; Z. Zakaria (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2015)
In Malaysia, thousands of kilometers of Optical Ground Wire (OPGW) have been installed by a utility company. For long distance fiber cable, there is a possibility of optical fiber to bend with very small radius especially in joint closures which caused optical power to attenuate. This attenuation is known as ‘bend losses. Bend loss increases the total power attenuation of optical fiber. In addition, for long distance fiber cable, it is important to avoid any extra loss as the fiber itself attenuates 0.2 to 0.35 dB/km and splice loss about 0.1 dB each. Hence, in this study, the method of detecting bend loss as well as optical fiber bending is presented. The result of this study is expected to allow fiber industry players to determine the exact location and proper rectification can be done to solve bend loss problem.